PROMOSI DIGITAL OBJEK WISATA TELAGA AIR MERAH DESA TANJUNG KABUPATEN KEPULAUAN MERANTI - Kurniati, Dwi; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Tanjung Village is a village located in one of the districts in Riau, namely Meranti Islands Regency, precisely in the city of Sealtpanjang which is quite famous and has the potential to become a tourist destination for the Meranti people. Telaga Air Merah Village focuses on managing the reservoir so that water tourism is definitely the main choice. Many Meranti residents spend their time off work to unwind at Telaga Air Merah, especially teenagers who enjoy capturing Instagrammable pictures. This research aims to see how promotions are implemented through digital media used by the management and the Telaga Air Merah tourism awareness group. In addition, it aims to find out what obstacles are faced by the management in this research using a qualitative descriptive method. The concept of this research uses Management theory. In collecting data, researchers used interview techniques, observation, literature study and documentation using key informants and supporters as sources of data information. The results of the research show that the implementation of promotions through digital media at the Telaga Air Merah tourist attraction still needs a lot of improvement, especially in the field of introducing digital media promotions. This is proven by the implementation not running as it should in the management of the tourist attraction. Apart from that, the management must increase the participation of Pokdarwis members and local residents. Keywords: Pomosi, Digital Media, Tanjung Village